(untitled) (Bangladesh Journal of Botany, 2020)
Investigation was undertaken to screen out the extract of botanicals viz., neem leaf, neem oil, garlic, marsh paper plant, allamanda leaf, wood apple leaf, betel leaf and biological antagonists viz., Trichoderma viride and T. harzianum. Positive control was soil amendment with Provax and negative control with untreated soil. Soil drenching with Provax and untreated soil showed 7.65 and 37.5% wilt of tomato. Wilt incidence varied from 8.5 - 30.81%. Botanicals and biocontrol agents had significant effect on yield of tomato. Provax gave the highest (30.55 t/ha) yield which was statistically identical to garlic extract (29.66 t/ha) and untreated control showed the lowest (20.19 t/ha) yield which was followed by soil drenching with neem leaf extract. Both the biocontrol agents viz., T. harzianum and T. viride as broth and compost significantly reduced wilt incidence of tomato in the field over control.